PENGARUH NILAI MEREK DAN PREFERENSI MEREK TERHADAP KEPUTUSAN ORANG TUA DALAM PENDAFTARAN SISWA (STUDI KASUS PADA PONDOK PESANTREN KUN KARIMA PANDEGLANG) - Muhammad Syifar Rahman; Pipin Suryanisari (Universitas La Tansa Mashiro, 2024)
This study aims to determine the effect of brand values and brand preferences on parents' decisions on student registration at the Kun karima pandeglang Islamic boarding school. The method used in this research is quantitative method with questionnaire data collection techniques, interviews,. The sample in this study were the guardians of class 1 MTs at Pondok Pesantre Kun Karima Pandeglang, totaling 35 respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. The statistical tests used were data normality tests, heteroscedasticity, multicollinearity, autocorrelation, multiple linear regression analysis, correlation coefficient analysis, determinant coefficient analysis, hypothesis testing (t test and f test) using the SPSS V 25 program. The results of this study indicate that Brand Value (X1) has a positive and significant effect on Parents' Decision on student enrollment (Y), Brand Preference (X2) has a positive and significant effect on Parents' Decision on Student Enrollment (Y), Brand Value (X1) and Brand Preference ( X2) has a positive effect on Parents' Decisions on Student Registration (Y).